2011
DOI: 10.1590/s1984-70332011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the mating system of Tucumã palm using microsatellite markers

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 16 publications
4
23
0
3
Order By: Relevance
“…(Ottewell et al 2012). This result also suggests that this species has an outcrossing reproductive system, which may be inferred since the application of molecular markers in adult plants and their progenies in species of the same genus detected this type of reproductive strategy (Eguiarte et al 1992, Ramos et al 2011. In this study, private alleles were observed for all three populations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…(Ottewell et al 2012). This result also suggests that this species has an outcrossing reproductive system, which may be inferred since the application of molecular markers in adult plants and their progenies in species of the same genus detected this type of reproductive strategy (Eguiarte et al 1992, Ramos et al 2011. In this study, private alleles were observed for all three populations.…”
Section: Discussionsupporting
confidence: 63%
“…The transferability of the primers was possible as a result of the homology between the genomes of these two species of the same genus. This homology was also found in the case of SSRs developed for peach-palm (Bactris gasipaes Kunth) that were transferred for use in tucumã palm (Astrocaryum aculeatum) (Ramos et al 2011), as well as the species cited in the review by Kalia et al (2011).…”
Section: Discussionmentioning
confidence: 58%
“…In a review, Husband and Schemske (1996) found general support for the theoretical prediction that, for outcrossing species, inbreeding depression tends to be expressed at early life stages. Although, there is no information on the mating system of A. murumuru and A. paramaca, close relatives, including A. mexicanum (Eguiarte et al, 1992) and A. aculeatum, are outcrossing (Ramos et al, 2011), and Oliveira NP, Oliveira MSP, Davide LC, Kalisz S (unpublished results) indicate that A. vulgare is outcrossing as well. Given the life history, floral and ecological traits shared by A. murumuru and A. paramaca with A. vulgare are likely all outcrossing.…”
Section: Discussionmentioning
confidence: 99%
“…All three species are monoecious, perennial, produce fleshy fruits containing a single seed, and their inflorescences are composed of separate male and female flowers distributed in dyads and triads (Kahn, 2008). The mating system of A. aculeatum was classified as outcrossing (Ramos et al, 2011). To date, there is no information on the mating system of the other two species studied here.…”
Section: Study Species Sampling Sites and Plant Materialsmentioning
confidence: 99%
“…Total DNA was extracted with the cationic detergent CTAB (2% cationic hexadecyl trimethyl ammonium bromide), as proposed by Doyle and Doyle () and then quantified in GelRed (Biotium) (Ramos et al., ). Eighteen microsatellite loci developed for E. precatoria (Epr01, Epr02, Epr04, Epr05, Epr06, Epr13, Epr14, Epr15, Epr18, Epr19, Epr21, Epr22, Epr27, Epr31, Epr32, Epr33, Epr35, and Epr36) were used in the study (Ramos, Dequigiovanni, Lopes et al., ).…”
Section: Methodsmentioning
confidence: 99%